JUAL BELI ANTARA SUAMI ISTRI MENURUT HUKUM ISLAM DAN KUH PERDATA PASAL 1467 - Revita Mala; Zul Anwar Azim Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
Buying and selling between husband and wife is one of the developments of transactions that occur in society in the form of an agreement in which the husband makes a buying and selling transaction to his wife either as a seller or as a buyer. The problems discussed in this study are about the legal status and similarities and differences in buying and selling between husband and wife according to Islamic law and the Civil Code article 1467. Research on this writing was conducted using the normative juridical method through the library research method. The results of this study can be concluded that, in Islamic Law, buying and selling between husband and wife is permissible, this is in accordance with the rules of fiqh specifically in the field of muamalah, it is stated that, the original law in all forms of muamalah is permissible unless there is evidence that prohibits it. While in the Civil Code, buying and selling between husband and wife is expressly prohibited and is only permitted for those who have an agreement on the separation of wealth. The difference between buying and selling between husband and wife in Islamic law and the Civil Code is that buying and selling between husband and wife in Islamic law is not expressly regulated, while in the Civil Code it is expressly regulated as contained in article 1467. The similarity is that in Islamic law and the Civil Code both regulate the existence of an agreement on the separation of marital property. Thus the fundamental difference in the approach of Islamic law and positive Indonesian law, as well as the need for a proper understanding of the legal position of each in the context of an agreement between husband and wife.